FPGA Implementation of the Bilinear Interpolation Algorithm for Image Demosaicking - Fuentes, Ivan Olaf Hernandez; Bravo-Zanoguera, Miguel Enrique; Yanez, Guillermo Galaviz (2009 International Conference on Electrical, Communications, and Computers, 2009)
Current image sensors offer a raw output that incorporates a bayer color filter pattern, and additional processing is required to obtain a full color image. This paper presents a bilinear interpolation algorithm to demosaick images with bayer color pattern; the algorithm is implemented in a single field programmable gate array (FPGA) device using a pipelined architecture. A comparison between images obtained with the FGPA-based interpolation and a software-based interpolation using Matlab demosaicking function is presented. The proposed FPGA demosaick algorithm achieves reasonable image quality, and it is an economic alternative for smart camera devices.